2015
DOI: 10.1021/acs.jpcc.5b03531
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Optical Properties of Graphene Quantum Dots: A Computational Study

Abstract: Because of the advantages of tunability via size, shape, doping, and relatively low level of loss and high extent of spatial confinement, graphene quantum dots (GQDs) are emerging as an effective way to control light by molecular engineering. The collective excitation in GQDs shows high energy plasmon frequency along with frequencies in the terahertz (THz) region, making these systems powerful materials for photonic technologies. Here, we report a systematic study of the linear and nonlinear optical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 60 publications
3
58
1
Order By: Relevance
“…In Figure 6 (a) the correlation between the gap energy and the inverse square root of the number of atoms is depicted. The general observation is a decrease in the gap energy with increasing the size due to quantum confinement 71 , also found in previous calculations 22,42,72 . This explains the red-shift in the absorption spectra.…”
Section: B Electronic Structuresupporting
confidence: 84%
See 2 more Smart Citations
“…In Figure 6 (a) the correlation between the gap energy and the inverse square root of the number of atoms is depicted. The general observation is a decrease in the gap energy with increasing the size due to quantum confinement 71 , also found in previous calculations 22,42,72 . This explains the red-shift in the absorption spectra.…”
Section: B Electronic Structuresupporting
confidence: 84%
“…The electronic structure of the system was described using the self-consistent charge density functional tight binding (SCC-DFTB) method, which is based on a second-order expansion of the Kohn-Sham energy around a reference density of the neutral atomic species 54 . This method has been extensively used for the study of graphene and graphene-based structures 26,31,38,42,53,55 and has been benchmarked with respect to DFT for several graphene based systems with defects, with bond length discrepancies around 2% and formation energies matching DFT values within 1.5% 56 . We have used the DFTB+ implementation of DFTB 57 , with the mio-1-1 set of parameters 58 , to obtain the hamiltonian, overlap matrix and the initial ground state (GS) single-electron density matrix.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[23][24][25][26][27][28][29][30][31] Recently, Yamijala et al studied the nonlinear optical properties of G-QDs and found that QDs with zigzag edges show interesting optical properties. 32 The tunability of the emission of QDs has been recently analysed considering the effect of different functional groups. 18 Herein, we evaluate the effect of the OH functionalisation on the ionisation potentials, absorption and emission properties of GO-QD zigzag edge models.…”
Section: A Introductionmentioning
confidence: 99%
“…In our earlier work, we studied in details the edge state transition and how ground state spin multiplicity plays a crucial roles. 34 Main point is that for all shaped GQDs, with different edges the strength of the coherent peak increases with the system size, with lowering of transition energy (also see S.I.). Fig.1(b) shows the difference between fundamental nature of the coherent peak and the peak generated from the edge states transition as the oscillator strengths of the edge states remain more or less unchanged with increase of the size of the system, while the oscillator strengths of the coherent peaks increase steadily with the system size due to more and more positive in-phase combination of the transition dipoles of the de-localized states (also see S.I.…”
Section: Resultsmentioning
confidence: 84%